2018
DOI: 10.5489/cuaj.5207
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three different antibiotic protocols in transurethral resection of bladder tumour and the possible infectious risk factors: A non-randomized, prospective study

Abstract: Those patients that only received a single dose of antibiotic before TURBT may have an increased risk of re-hospitalization due to fever in comparison to those who received prolonged antibiotic protocols. In addition, there are perioperative factors in this surgery that predict the risk of infectious complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…In 2018, Navarette published a study in which he investigated 216 patients who underwent TUR-BT and followed 3 different antibiotic prophylaxis protocols, similar to the groups in the present study, with the difference being that in the third group antibiotic therapy was continued at home for 5 days after discharge. The study concluded that the patients who received single-dose antibiotic prophylaxis before TUR-BT had a higher risk of rehospitalization for fever in comparison to those who received prolonged antibiotic therapya fact that was also confirmed by the present study [34]. Moreover, according to the above study, tumour necrosis, the number of tumours and a longer hospital stay might predispose the patients to develop infectious complicationsa finding that was not proved by the present study.…”
Section: Resultssupporting
confidence: 63%
“…In 2018, Navarette published a study in which he investigated 216 patients who underwent TUR-BT and followed 3 different antibiotic prophylaxis protocols, similar to the groups in the present study, with the difference being that in the third group antibiotic therapy was continued at home for 5 days after discharge. The study concluded that the patients who received single-dose antibiotic prophylaxis before TUR-BT had a higher risk of rehospitalization for fever in comparison to those who received prolonged antibiotic therapya fact that was also confirmed by the present study [34]. Moreover, according to the above study, tumour necrosis, the number of tumours and a longer hospital stay might predispose the patients to develop infectious complicationsa finding that was not proved by the present study.…”
Section: Resultssupporting
confidence: 63%
“…Nevertheless, despite the current evidence, tumor necrosis is not yet an independent predisposing factor to infection. (12) Limitations to our study included the fact that patients with a pre-procedure PUC were…”
Section: Discussionmentioning
confidence: 99%
“…(10) There is still no consensus on the use of antibiotic pro-phylaxis regarding TURBT, despite the fact that it is a frequent procedure. (12) The aim of the present study was to analyze the microbiology and incidence of drug resistance in patients that underwent TURBT and to identify independent risk factors for postoperative UTI.…”
Section: Introductionmentioning
confidence: 99%